Technological Horizons : insights for accounting, auditing and internal control in emerging markets - Alshurafat, Hashem; Beattie, Claire (Technological innovation and sustainability for business competitive advantage, 2025)
Adopting AI in accounting, auditing and internal control comes with challenges that need to be addressed for successful implementation. Key challenges include data quality, lack of understanding, regulatory compliance, ethical concerns, cost of implementation, resistance to change, security concerns, and scalability issues. Addressing these challenges requires a comprehensive and collaborative approach involving technology experts, regulatory bodies, and accounting professionals. The research presented connects traditional accounting, auditing and internal control practices with the cutting-edge technological advancements that are revolutionizing the way business transactions are conducted. Emerging technologies such as artificial intelligence, blockchain, data analytics, and automation have transformed the way financial information is processed, requiring professionals in these domains to develop new skill sets. Technological Horizons: Insights for Accounting, Auditing and Internal Control in Emerging Markets delves into the heart of these transformations and offers interdisciplinary insights that can inform and guide the adaptation of accounting and auditing practices in a tech-driven era. Technological Innovation and Sustainability for Business Competitive Advantage series emphasizes the scientific exploration of business challenges faced by organizations, while offering practical solutions. By contributing to the development and enhancement of business theories and practices, and by promoting scientific research in technological innovation and sustainability, the volumes facilitate meaningful dialogues among academics, practitioners, and individuals. The research presented connects traditional accounting, auditing and internal control practices with the cutting-edge technological advancements that are revolutionizing the way business transactions are conducted.